2007
DOI: 10.1158/1535-7163.mct-07-0148
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the mitogen-activated protein kinase pathway results in the down-regulation of P-glycoprotein

Abstract: The multidrug resistance gene 1 (MDR1) product, P-glycoprotein (P-gp), pumps out a variety of anticancer agents from the cell, including anthracyclines, Vinca alkaloids, and taxanes. The expression of P-gp therefore confers resistance to these anticancer agents. In our present study, we found that FTI-277 (a farnesyltransferase inhibitor), U0126 [an inhibitor of mitogen-activated protein kinase/extracellular signal-regulated kinase (ERK) kinase (MEK)], and 17-allylamino-17-demethoxygeldanamycin (an inhibitor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 30 publications
11
117
0
Order By: Relevance
“…The role of the ERK pathway in the generation of multidrug resistance has received more consideration than in the past. Previous studies demonstrated that the modulation of ERK activation may be a novel method used to reverse multidrug resistance (15). In the present study, the changing pattern of p-ERK was similar to that of p-Aurora A and P-gp; accordingly, p-Aurora A is proposed to regulate P-gp through p-ERK.…”
Section: P-erk-mediated Down-regulation Of P-gp In Mx-1/taxol Cells Tsupporting
confidence: 74%
“…The role of the ERK pathway in the generation of multidrug resistance has received more consideration than in the past. Previous studies demonstrated that the modulation of ERK activation may be a novel method used to reverse multidrug resistance (15). In the present study, the changing pattern of p-ERK was similar to that of p-Aurora A and P-gp; accordingly, p-Aurora A is proposed to regulate P-gp through p-ERK.…”
Section: P-erk-mediated Down-regulation Of P-gp In Mx-1/taxol Cells Tsupporting
confidence: 74%
“…It is well known that inhibition of the MEK-ERK-RSK pathway down-regulates P-gp expression levels and diminishes cellular multidrug resistance (24,28). Our studies demonstrated that ezhu and yanhusuo extracts exert a significant synergistic effect on inhibiting phosphorylation of ERK1/2 protein.…”
Section: Discussionsupporting
confidence: 53%
“…The development of MDR is often accompanied by the modulation of MAPKs (24)(25)(26). ERK1 and 2 are known to act as anti-apoptotic cascades by transducing survival signals, whereas JNK or p38 phosphorylation results in the promotion of apoptosis (27).…”
Section: Discussionmentioning
confidence: 99%